Biologic activity and treatment resistance to gastrointestinal cancer: the role of circular RNA in autophagy regulation - Zhang, Bo; Li, Zhe; Ye, Guoliang; Hu, Kefeng (Frontiers in Oncology, 2024)
Circular RNAs (circRNAs) lack the 5’-end methylated guanine cap structure and 3’ polyadenylate tail structure, classifying it as a non-coding RNA. With the extensive investigation of circRNA, its role in regulating cell death has garnered significant attention in recent years, establishing it as a recognized participant in cancer’s biological processes. Autophagy, an essential pathway in programmed cell death (PCD), involves the formation of autophagosomes using lysosomes to degrade cellular contents under the regulation of various autophagy-related (ATG) genes. Numerous studies have demonstrated that circRNA can modulate the biological activity of cancer cells by influencing the autophagy pathway, exhibiting a dualistic role in suppressing or promoting carcinogenesis. In this review, we comprehensively analyze how autophagy-related circRNA impacts the progression of gastrointestinal cancer (GIC). Additionally, we discuss drug resistance phenomena associated with autophagy regulation in GIC. This review offers valuable insights into exploring potential biological targets for prognosis and treatment strategies related to GIC.